Ecuador-Brazil trade relations: a board without bishops - Ortiz Arroba, Francisco (2010)
Since September 2008 bilateral trade relations between Ecuador and Brazil have been damaged after the expulsion of Odebrecht company and a loan payment suspension with National Development Bank of Brazil. The essay shows that Ecuador’s politically-driven domestic concerns behind those decisions have worsen the negative trade balance of Ecuador with Brazil.